1951
DOI: 10.1002/zaac.19512660607
|View full text |Cite
|
Sign up to set email alerts
|

Metallamide und Metallnitride, 25. Mitteilung. Zur Kenntnis des Lithiumimides

Abstract: Es wurde Lithiumimid durch thermische Zersetzung des Amides hergestellt. Seine Dichte ist 1,48. Li2N kristallisiert dem CaF2 antiisomorph, ist also dem Li2O isomorph; es hat die Gitterkonstante 5,047 Å. Der univalente Radius des NH2−‐IOs ist 2,00 Å. Durch tensimetrische Untersuchung wird festgestellt, daß Lithiumamid kein Ammoniakat bildet. Das Amid gibt zunächst einphasig Ammoniak ab, es schließt sich ein Zweiphasengebiet an, bestehend aus einem ammoniakarmen Amid‐Mischkristall und dem Lithiumimid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
59
0

Year Published

1964
1964
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(65 citation statements)
references
References 3 publications
5
59
0
Order By: Relevance
“…Two broad peaks were observed at 2θ = 31 • and 52.5 • in addition to the peaks of GaN and LiH and very small peaks of Li 3 GaN 2 . These two peaks were probably related to the 1 1 1 and 0 2 2 of Li 2 NH (cubic, a = 5.047Å, Fm-3m) [15], but they were shifted at higher diffraction angles. The lattice parameter calculated from the peak positions was 4.96Å.…”
Section: Resultsmentioning
confidence: 95%
“…Two broad peaks were observed at 2θ = 31 • and 52.5 • in addition to the peaks of GaN and LiH and very small peaks of Li 3 GaN 2 . These two peaks were probably related to the 1 1 1 and 0 2 2 of Li 2 NH (cubic, a = 5.047Å, Fm-3m) [15], but they were shifted at higher diffraction angles. The lattice parameter calculated from the peak positions was 4.96Å.…”
Section: Resultsmentioning
confidence: 95%
“…The effect appears to be nearly saturated at 11 mg, and it does not continue to still larger sample sizes; ∼350 mg LiNH 2 samples measured in the high-pressure TGA apparatus have decomposition rates that are comparable to these values. A likely explanation for this behavior lies in the very low equilibrium vapor pressure of NH 3 for the LiNH 2 decomposition reaction [8]. At 300 • C, for example, an NH 3 partial pressure of ∼1 kPa is sufficient to inhibit LiNH 2 decomposition.…”
Section: Resultsmentioning
confidence: 98%
“…In analogy with NaAlH 4 , Ichikawa et al [7] found that the kinetics of hydrogen release near 200 • C were improved by incorporating TiCl 3 into mixed LiNH 2 + LiH powders. Of critical importance for application of Li-N-H materials to hydrogen storage is the existence of a competing reaction in which lithium amide decomposes by releasing ammonia [8]:…”
Section: Introductionmentioning
confidence: 99%
“…The Li 2 O amorphous-like phase, which diffraction peak width is broader and lattice constant is larger than Li 2 O crystalline phase, mostly changed into the crystalline phase during the heat treatment. It has been reported that the crystal structure of Li 2 NH is anti-fluorite type structure (space group Fm3m) consisting of Li + and NH 2− [14]. However, hydrogen atom positions in Li 2 NH crystal have not yet been determined.…”
Section: Crystal Structure Of LI 2 Nhmentioning
confidence: 97%